Pengaruh Investasi, Inflasi, Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Di Provinsi Aceh - Akmalia, Rizki; Sabrina, Putri; Munawar, Wali (Jurnal Samudra Ekonomika, 2024)
Economic Growth measures the achievements of a country's economic development. Inventory can be calculated by the amount of Economic Growth. This research aims to analyze the influence of investment, inflation and government spending in Aceh Province. This type of research is included in descriptive statistical research. The data used in this research is annual time series data from 2018-2022. The method used is multiple linear analysis. The regression equation in this research is Y = 1.014 + 0.887X1 + 0.256X2 + 0.330X3. Investment has a significant effect on Aceh's economic growth, where from the t test the t sig value is obtained. < 0.05 (0.022 < 0.05). Inflation has a significant effect on Aceh's economic growth, where from the t test the t sig value is obtained. < 0.05 (0.015 < 0.05). Government spending has a significant effect on Aceh's economic growth, where from the t test the t sig value is obtained. < 0.05 (0.019 < 0.05). Investment, inflation and government spending simultaneously have a significant effect on Aceh's economic growth, where from the t test the value of F sig is obtained. < 0.05 (0.000 < 0.05).